Prevalence of myopic macular degeneration worldwide: a systematic review and meta-analysis. Issue 12 (18th March 2020) - Zou, Minjie; Wang, Shibin; Chen, Aiming; Liu, Zhenzhen; Young, Charlotte Aimee; Zhang, Yichi; Jin, Guangming; Zheng, Danying
Abstract : Purpose: To investigate the prevalence of myopic macular degeneration (MMD) in the global population. Methods: All published literature of population-based studies on MMD prevalence worldwide were searched and only those with clear definitions to diagnose and classify MMD lesions by standardised grading methods were selected. Meta-analysis methods were used to calculate the pooled prevalence of MMD and its 95% CI in a random-effects model. The prevalence of MMD lesions would also be reported, together with the subgroup analysis of age, region and gender. Correlation between MMD prevalence and spherical equivalent levels and axial length were also evaluated. Results: 12 studies with 58 558 subjects were included in this meta-analysis. The pooled prevalence of MMD in the world population was 2.1% (95% CI: 1.3% to 3.3%). In the subgroup analysis, people with the following characteristics were at higher risk of developing MMD: female, urban life, living in Asia, older age, longer axial length and severer myopia. Conclusions: MMD is a serious public health concern worldwide, particularly in subjects who are women, subjects living in urban areas, subjects living in Asia, and subjects with longer axial lengths and severer myopia. Further studies from other continents/ethnicities are needed for comprehensive estimates of the prevalence of MMD globally.